1991
DOI: 10.1161/01.hyp.18.2.142
|View full text |Cite
|
Sign up to set email alerts
|

Captopril protects against myocardial injury induced by magnesium deficiency.

Abstract: We have previously reported that antioxidant drug intervention protects against magnesium deficiency-induced myocardial lesions. In the present study, Golden Syrian male hamsters were fed either a magnesium-deficient diet or a magnesium-supplemented diet Animals from each group received sulfhydryl-containing angiotensin converting enzyme inhibitors: captopril, epi-captopril (a stereoisomer of captopril), and zofenopril* (arginine blend of zofenopril containing a free SH group); another group of animals receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…28 Similarly, SH-containing ACE inhibitors also protect endothelial cells in vitro against exogenously generated free radicals, 3 and captopril, epicaptopril (a stereoisomer of captopril), and zofenopril all significantly protected male hamsters from cardiomyopathy due to Mg deficiency, whereas enalaprilat afforded only a slight (nonsignificant) protection. 12 Captopril and zofenopril have also been found to attenuate postischemic contractile dysfunction of the viable but stunned myocardium during the early hours after relief from ischemia, whereas there is no consensus on the effects of other ACE inhibitors. 29 In erythrocytes, captopril was protective against various oxidant stresses: hemolysis caused by 2,2Ј-azobis and hypochlorite, lipid peroxidation of erythrocyte membranes caused by tertbutyl-hydroperoxide (tBOOH) and hypochlorite, inactivation of erythrocyte membrane ATPases caused by tBOOH, and oxidation of hemoglobin caused by AAPH and tBOOH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Similarly, SH-containing ACE inhibitors also protect endothelial cells in vitro against exogenously generated free radicals, 3 and captopril, epicaptopril (a stereoisomer of captopril), and zofenopril all significantly protected male hamsters from cardiomyopathy due to Mg deficiency, whereas enalaprilat afforded only a slight (nonsignificant) protection. 12 Captopril and zofenopril have also been found to attenuate postischemic contractile dysfunction of the viable but stunned myocardium during the early hours after relief from ischemia, whereas there is no consensus on the effects of other ACE inhibitors. 29 In erythrocytes, captopril was protective against various oxidant stresses: hemolysis caused by 2,2Ј-azobis and hypochlorite, lipid peroxidation of erythrocyte membranes caused by tertbutyl-hydroperoxide (tBOOH) and hypochlorite, inactivation of erythrocyte membrane ATPases caused by tBOOH, and oxidation of hemoglobin caused by AAPH and tBOOH.…”
Section: Discussionmentioning
confidence: 99%
“…9 -11 A distinct, long-term Mg-deficient cardiomyopathy has been defined that can be reversed both by treatment with Mg and by the addition of SH-containing angiotensin-converting enzyme (ACE) inhibitors such as captopril but not by enalaprilat or by other non-SH converting enzyme-inhibiting compounds. 9,12 In all of these circumstances, the mechanism of this thiol group-related protective action of captopril, although presumed to be secondary to free radical scavenging and the subsequent decrease in reactive oxygen species, has yet to be defined.…”
mentioning
confidence: 99%
“…In fact, calcium channel block ers are known to have continued efficacy in long-term treatment of hypertension and are associated with reduced ventricular ectopy [16]. Also, nifedipine [17], like captopril [18], has been shown experimentally to protect against myocardial damage produced by mag nesium deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,36 Feeding rats and hamsters diets defi cient in Mg, for periods of only 14 to 21 days, results in cardiomyopathic lesions, cytokine formation and release (IL-1, IL-2, IL-6; TNFα), and endothelin formation. [40][41][42] Using human umbilical vein endothelial cells (HUVE), Maier and colleagues 43 44 have reported that Mg defi ciency in rats leads to a clinical type of infl ammatory syndrome characterized by increased production of leukocytes, release of several cytokines, macrophage activation, and production of acute phase infl ammatory proteins. Although other growth factors (PDGF, transforming growth factor B, fi broblast growth factors) have not yet been identifi ed in Mg-defi cient states, it is likely that Mg defi ciency will be found to cause production of these wellknown growth factors implicated in atherogenesis.…”
Section: Low Magnesium Levels Can Lead To Formation Of Pro-inflammatomentioning
confidence: 99%